Paul’s Understanding of the Resurrection in 1 Corinthians 15:36–54 - Ware, James P. (Journal of Biblical literature, 2014)
The present essay contributes to the current discussion regarding the nature of the resurrection in 1 Corinthians 15. The article begins with a capsule summary of the chapter’s history of interpretation, which is generally unfamiliar to NT scholars but provides crucial perspective on the current discussion. The article then offers a new proposal regarding the literary and syntactic structure of Paul’s exposition of the resurrection body in 1 Cor 15:36–54. Building on prior structural analysis of the text, the essay points to key but previously neglected features of the passage’s composition, arguing that the specific way in which Paul shapes his exposition has crucial implications for his understanding of the nature of the resurrection event. In concert with this structural analysis, the article also seeks to advance scholarly discussion of two much-debated elements of Paul’s thought in the passage, providing a fresh discussion of the nature of the “change” that Paul envisions in 15:51–52, and an analysis of Paul’s description of the risen body as a sōma pneumatikon in 15:44. The structure of Paul’s argument in 1 Cor 15:36–54 proposed here has, I argue, significant ramifications for the long-standing debate regarding the nature of the resurrection in Paul.